(3GdOQQ GdZQhjI aj TQM GddeYI GdOeTbjIs - (3MSf Hf Ydj GdNGbGfjs
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdYGdejf (B... (3cJGH GdRcGI GdJj hLhHgG ef VQhQjGJ GdOjf hefcQg eY GdYde Hg cGaQ hjTJQW aj hLhHgGs
(3BNQgG (B:s
(3BNQgG(B: (3adh cGf Ydjg CUhY dLeGYI jLhR QaYgG ef ZjQ JYjjf Cf gPG GdadGf hgPG GdadGf HdG QjH(B. (3Je cJGH GdRcGI eSJhai HHQcGJ CTQa Ndbgs
(3JHUQI GdYfhGf (B:s
(3gPG GdYfhGf gh GdehLhO HHWGbI GdagQSI, hCXfg LRA ef cJGH cHjQ aj Gdabgs
(3JHUQI GdeDda (B:s
(3gcPG aj HWGbI GdagQSI hde CLO dg JhKjbs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis